A Comparative Analysis of Family-Focused and Metacognitive Therapies to Improve Parental Affective Regulation in Bipolar II Youth - Hoda Hasani; Mahmoud Goudarzi; Parviz Karimisani (Caspian Journal of Health Research)
Background: Bipolar II disorder in children has a significant impact on family dynamics, often leading to parental stress and difficulties in affective control. These parental challenges can exacerbate the child's symptoms and hinder treatment outcomes. Objectives: This study aimed to compare the effectiveness of Family-focused therapy (FFT) and metacognitive therapy (MCT) on affective control in parents of children diagnosed with bipolar II disorder. Methods: This study utilized a quasi-experimental design with a pre-test, post-test, and 3-month follow-up assessment. A convenience sample of 45 individual parents of children diagnosed with bipolar II disorder, who were seeking counseling services in Isfahan, Iran (2023), was recruited for this study. Participants were subsequently assigned to one of three groups: FFT (n=15; 7 mothers, 8 fathers), which consisted of nine 120-minute sessions; MCT (n=15; 8 mothers, 7 fathers), which comprised eight 120-minute sessions; or a wait-list control group (n=15; 7 mothers, 8 fathers). Affective control was measured using the Affective Control Scale at pre-test, post-test, and follow-up. Data were analyzed using repeated measures ANOVA (SPSS v. 26). Results: Based on the results, both FFT and MCT led to improvements in parental affective control components at the post-test stage compared to the control group (P<0.001). Furthermore, the results of group comparisons indicated a significant difference between the effects of FFT and MCT on the components of depressed mood (P=0.041), anxiety (P=0.044), and the overall affective control score (P=0.006). These findings suggest that FFT was a more effective method than MCT for enhancing affective control.